Anomalous functional connectivity within the default-mode network in treatment-naive patients possessing first-episode major depressive disorder. Issue 23 (11th June 2021) - Yu, Renqiang; Tan, Huan; Peng, Gang; Du, Lian; Wang, Peijia; Zhang, Zhiwei; Lyu, Fajin
Abstract: Background and Objective: Previous studies have shown that the default-mode network (DMN) has a substantial role in patients with major depressive disorder (MDD). However, there is a shortage of information regarding variations in the functional connectivity (FC) of the DMN of treatment-naive patients with first-episode MDD. The present study aims to explore the FC of the DMN in such patients. Methods: The study population consisted of 33 patients and 35 controls, paired regarding age, gender, education level, and health condition. Depression severity was assessed through the Hamilton Depression Scale (HAM-D), and subjects underwent evaluation during the resting-state through functional magnetic resonance imaging (rs-fMRI). To assess the result, we used FC and ICA. We used Spearman's correlation test to detect potential correlations between anomalous FC and severity of HAM-D scores. Results: We have found a decreased FC in the left medial orbitofrontal gyrus (MOFG) and right marginal gyrus (SMG) in depressive patients compared to controls. There was a negative correlation between abnormal FC in the right SMG and HAM-D scores. We have not found any increase in FC of the DMN in treatment-naive, first-episode of MDD patients. Conclusions: Our study provided evidence of a negative correlation between abnormal FC in the DMN and severity of depression symptoms measured by HAM-D in treatment-naive MDD patients. This finding could shed some light on the relevance of DMN for understanding the pathophysiology of cognitive impairment in MDD.